Peningkatan Kreativitas Belajar Melalui Penerapan Model Project Based Learning Pada Siswa kelas IV SDN 13 Mataram - Masita, Adi (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This research aims to determine 1) teacher activities using the Project Based Learning model in class IV SDN 13 Mataram 2) student activities using the Project Based Learning model in class IV SDN 13 Mataram, 3) Student learning creativity using the Project Based Learning model in class IV SDN 13 Mataram. This research method uses Classroom Action Research (PTK). The subjects in this research were all class IV students at SDN 13 Mataram for the 2023/2024 academic year, consisting of 27 students. The instruments used in this research were teacher activity observation sheets, student activity observation sheets, and student creativity observation sheets. Then this data is analyzed using the percentage formula. Based on the results of data analysis obtained by teacher activities in cycle I, the average score was 71.76% in the good category and increased in cycle II, the score was 94.11% in the very good category. Meanwhile, student activity in cycle I scored 70% in the good category, and increased in cycle II to get a score of 92.5% in the very good category. From managing the level of student creativity in cycle I, the score was 65.21% in the quite creative category and increased in cycle II to 86.96% in the creative category. In this way, the Project Based Learning model can increase student learning creativity in class IV SDN 13 Mataram